The Knowledge Level of Students at the Faculty of Dental Medicine, Universitas Airlangga Regarding the Forensic Odontology Field - Chusida, An'nisaa; Rizky, Beta Novia; Kurniawan, Arofi; Pantoro, Jennifer Natasha; Setiyono, Nabila Firdausi Rizki; Gatra, Mumtaz Ramadhani Putra Pesat (Indonesian Journal of Dental Medicine, 2025)
Background: Forensic odontology is a field concerned with the use of dental evidence to identify the age, race, gender of victims and suspects in mass disasters, abuse, and organized crime. General dentists are required to have basic knowledge and expertise in forensic dentistry. Aspiring dentists in dental professional education must demonstrate mastery in both medical and dental sciences, which is a requirement to fulfill the dentist competency standard. Forensic dentistry supports preclinical and clinical skills in both basic and applied dentistry. Therefore, research is necessary to determine the level of knowledge of undergraduate dental students, dental professional education students, and dental specialist program students regarding the field of forensic odontology. Information about the level of knowledge was obtained by using a questionnaire that inquired about the content of the material measured. In this study, the research subjects were undergraduate dental students, dental professional education students, and dental specialist program students at the Faculty of Dental Medicine, Universitas Airlangga. Purpose: Analyze the level of knowledge of students at the Faculty of Dental Medicine, Universitas Airlangga, regarding the field of forensic odontology. Methods: This study is an analytical observational study with a cross-sectional research design. This study used Google Forms for data collection with closed questionnaires. Results: According to the results of this study, a significant majority of respondents, specifically 83.3%, demonstrated a level of knowledge in the good category. Conclusion: the Faculty of Dental Medicine, Universitas Airlangga students had knowledge levels in a good category regarding the field of forensic odontology.